Pewaris Al-Qur’an Presfektif Mufassir Nusantara (Analisis Surah Fathir Ayat 32) - Simamora, Irfan Mansyur (ANWARUL, 2024)
In Q.S Fathir verse 32 it is stated that Allah bequeathed the Koran to the servants he chose using the phrase Isthofa, namely the best servant among other servants. However, it is also explained that among them there are those who oppress themselves (Dzholimul linafsih), there are those who are middle (Muqtasidah), and there are those who do all good deeds first (Saabiqum Bilkhairot) with the permission of Allah SWT. According to some Indonesian commentators, including Buya Hamka, Quraish Shihab and Hasbi Ash Siddiqey, the heirs of the Qur'an are the people of Muhammad SAW who believe in Allah and His Messenger. The dzholim are the ummah who carry out Allah's prohibitions contained in the Qur'an but do not reach the point of disbelief, the muqtasidah are the ummah who sometimes carry out Allah's commands and sometimes leave them, while the saabiqum bilkhairot are the ummah who first do all good deeds with Allah's permission swt. The three Mufassir of the archipelago agreed that as long as the three groups did not associate partners with Allah and His Messenger, they would still receive Allah's grace even though sometimes there were those among them who oppressed themselves, because Allah had glorified the ummah of Muhammad beyond the glory obtained by the previous ummah. And these three groups are the best servants chosen by Allah SWT as inheritors of the Qur’an.